Internal Communication in Pharmaceutical Companies: A Case Study of Portuguese Companies during the Pandemic of COVID-19 - Andreia Garcia (Communication & Society (Formerly Comunicación y Sociedad))
While companies across different sectors in the Western world have increasingly begun to value their employees’ roles, this practice is not yet universal in our globalized economy. This research examines how the COVID-19 pandemic influenced employee communication practices within pharmaceutical companies operating in Portugal. Through a survey of communication managers, our findings reveal that these companies not only shifted to online communication channels during the pandemic but continue to maintain these digital platforms as primary communication tools.